The influence of social relationships on substance use behaviors among pregnant women with opioid use disorder. (1st May 2021) - Asta, Dena; Davis, Alex; Krishnamurti, Tamar; Klocke, Leah; Abdullah, Walitta; Krans, Elizabeth E.
Highlights: Pregnancy has a profound influence on women's substance use behaviors. Changes in social relationships due to pregnancy may affect substance use behaviors. Network members who use substances may adversely affect substance use in pregnancy. Abstract: Objective: To describe the social network characteristics of pregnant women with opioid use disorder (OUD) and explore how changes in social relationships during pregnancy may influence substance use behaviors. Methods: Between 2017 and 2018, we conducted an exploratory pilot study among 50 pregnant women with OUD. Participants completed a detailed social network inventory to describe the behaviors (e.g. substance-using), social support characteristics (e.g. financial, emotional, informational) and roles (e.g. family member, friend) of network members. The primary outcome was a self-reported decrease in substance use during pregnancy. Pearson correlations were used to test for associations between covariates reflecting different aspects of participants' social networks and decreased substance use during pregnancy. Results: Most participants (84.0 %) decreased substance use during pregnancy and stated that pregnancy motivated them to engage in treatment (94.0 %). Participants had a median of 8 (IQR: 4−18) network members with differing proportions of those who did and did not use substances. Pregnancy prompted participants to significantly increase contact with (26.4 % vs. 5.0 %), have increased support from (35.7 % vs. 7.5 %), and a have a feeling of increased closeness with (26.1 % vs. 3.3 %) network members who did not use substances. However, decreased substance use during pregnancy was most strongly (negatively) associated with the proportion of network members who used substances and provided informational support (r=-0.25, p = 0.08) and a feeling of closeness (r=-0.26, p = 0.08). Conclusions: Our findings indicate that pregnancy has a profound influence on women's substance use behaviors and that changes in social relationships due to pregnancy may influence substance use.